ISOLATION AND MOLECULAR DETECTION OF ARTHROBACTER SPECIES GROWN ON THE SURFACE OF DATE PALM TISSUE CULTURE MEDIA - & et al., Abdulrazzaq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to found out the type of  bacterial species grown on the surface of date palm tissue culture media. Shoot tips of date palm (Barhi cv.) were cultured on MS media supplemented with various combinations of hormones. During  growth an infection was appeared in all cultures with gray colour. Primarily identification, proved  a bacterial infection due to its colour and appearance. The genus Arthrobacter was isolated Antibiotic sensitivity test showed that the isolate was sensitive to ciprofloxacin,Trimethoprim, and Amikacin and resistant  to Clarithromycin,Ceftriaxone and Gentamycin. Sequence analysis of 16 rRNA indicated a new isolates   were closely related to the  Glutamicibacter  arilaitensis strain ebst40 and Arthrobacter arilaitensis  strain L11 with the  highest sequence similarity (100%) .